Analisis Internet Financial Reporting Index; Studi Komparasi Antara Perusahaan High-tech dan Non High-tech di Indonesia - Nadia Shelly Wardhanie (Jurnal Reviu Akuntansi dan Keuangan, 2012)
The purpose of this study was to compare the IFR disclosure between high-tech companies and non high-tech companies in Indonesia. IFR index consists of four components, namely content, timeliness, technology and user support. Object of this study were 19 high-tech companies and 19 non high-tech companies in Indonesia. These results indicate that there is no difference between the IFR disclosure between high-tech companies and non high-tech companies in Indonesia. the average number of IFR disclosure on high-tech company for 20.63 or 53%, while the average non-disclosure in high-tech company for 18.37 or 47%. Mann-Whitney test results to explain the test score Asymp. Sig. (2-tailed) is 0.529 indicates that there is no significant difference.